2019
DOI: 10.1634/theoncologist.2018-0676
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of DLL3 and ASCL1 in Surgically Resected Small Cell Lung Cancer (HOT1702)

Abstract: Background Delta‐like protein 3 (DLL3) is a Notch ligand that has an important role in the tumorigenesis of small cell lung cancer (SCLC). Recently, rovalpituzumab tesirine (Rova‐T), a DLL3‐targeted antibody‐drug conjugate, has been developed for treating SCLC. DLL3 is a transcriptional target of the achaete‐scute homolog‐1 (ASCL1) transcription factor, which is involved in pulmonary neuroendocrine cell development. However, the relationship between DLL3 and/or ASCL1 expression and the clinical features of SCL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
42
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 33 publications
10
42
2
Order By: Relevance
“…The positive expression rates of ASCL1 and NEUROD1 in our SCLC samples were similar to those found in previous reports [22,27]. The expression of the target molecules in the ASCL1-positive group was consistent with previous findings [31,[33][34][35][36][37][38][39][40][41][42]. As half of the candidate ASCL1-target molecules selected from the gene expression omnibus dataset showed significance in the IHC study of the ASCL1-positive samples, IHC could be a useful method for detecting candidate target molecules for the four key molecules.…”
Section: Discussionsupporting
confidence: 92%
“…The positive expression rates of ASCL1 and NEUROD1 in our SCLC samples were similar to those found in previous reports [22,27]. The expression of the target molecules in the ASCL1-positive group was consistent with previous findings [31,[33][34][35][36][37][38][39][40][41][42]. As half of the candidate ASCL1-target molecules selected from the gene expression omnibus dataset showed significance in the IHC study of the ASCL1-positive samples, IHC could be a useful method for detecting candidate target molecules for the four key molecules.…”
Section: Discussionsupporting
confidence: 92%
“…26 In high-grade neuroendocrine lung tumors (including small cell lung cancer (SCLC) and large-cell neuroendocrine cancer (LCNEC)), DLL3 is overactive at the tumor cell surface and positively correlates with achaete-scute homolog-1 (ASCL1), a member of the BHLH family of transcription factors that is involved in neuroendocrine cell fate decisions. [27][28][29] ASCL1 activates DLL3 by binding to special E-box sites in the DLL3 promoter, as observed in the dorsal neural tube. 30 In a recent study, LCNEC was divided into two molecular phenotypes based on the expression of DLL3 and ASCL1.…”
Section: Delta-like Ligands In Lung Cancermentioning
confidence: 86%
“…56 In GI-NEC, SCLC and SCBC, DLL3 shows a cytoplasmic distribution in tumor cells (reported as Golgi apparatus-localized in a single SCLC study 114 ) but how this influences Notch signaling is unknown. 27,28,112,113,[115][116][117] In LLC cells, DLL3 localizes to the cell nuclei, inhibiting Notch signaling at the transcriptional level. Akt signaling is activated by DLL3, which promotes LLC cell survival and reduces cell apoptosis.…”
Section: Dll3mentioning
confidence: 99%
“…Finally, we were left with 16 eligible studies after screening the full text, among which 6 articles were included in our final analysis ( Fig. 1) [20][21][22][23][24][25]. Ten articles were excluded for the following reasons: seven articles were review researches and commentaries, one article did not report hazard ratios and Kaplan-Meier curves and 2 articles were abstracts and did not report relevant outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…One interpretation of this result was that DLL3 expression varies between different populations. The American study indicated that the high expression of DLL3 was a marker of good prognosis [21], and there was no significant correlation between DLL3 expression and prognosis in several Japan studies [22,25], while the high expression of DLL3 is a marker of poor prognosis in China studies [20,23]. These results showed that the expression of DLL3 might be different in different populations.…”
Section: Discussionmentioning
confidence: 96%